Smart Mobility : The Government policy to boost the tourism sector through the Heritage Track Bus in Yogyakarta City - Pramudya Anggun Rahmani; Muhammad Eko Atmojo (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
This article examines the implementation of smart mobility policies through Heritage Bus Routes as a government strategy to strengthen sustainable tourism development in the city of Yogyakarta in the context of Society 5.0. This study analyzes how transportation innovations can be integrated with cultural heritage preservation to increase tourist participation and enhance visitor experiences in heritage cities. Using a descriptive qualitative approach, this study analyzes policy implementation, stakeholder collaboration, and user perceptions. Data were collected through in-depth interviews with key stakeholders, program users, and educators, and were supplemented by secondary data from the literature and official documents. This study was conducted between August and November at the Yogyakarta Special Region Cultural Office. Findings indicate that the heritage bus policy has largely achieved its objectives, reflected in tourist participation exceeding targets, route expansion, and consistent user satisfaction. Despite challenges such as limited fleet availability and a suboptimal reservation system, the program effectively integrates urban transportation with cultural heritage preservation along the Yogyakarta Philosophy Axis through educational tourism. Supported by strong stakeholder collaboration and positive public perception, the Heritage Bus represents an innovative model of smart mobility and provides a policy reference for other heritage cities.